A systematic review of the use of virtual reality and its effects on cognition in individuals with neurocognitive disorders. Issue 1 (1st January 2019) - Moreno, Alexander; Wall, Kylie Janine; Thangavelu, Karthick; Craven, Lucas; Ward, Emma; Dissanayaka, Nadeeka N.
Abstract: Introduction: Virtual reality (VR) interventions are increasingly used in individuals with brain injuries. The objective of this study was to determine the effects of VR on overall cognitive functioning in individuals with neurocognitive disorders (NCDs). Methods: Using Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines, a systematic review of the published literature on immersive and nonimmersive VR technologies targeting cognition in minor and major NCDs was conducted: (PROSPERO registration number: CRD42019121953). Results: A total of 22 studies were included in the review, for an aggregated sample of 564 individuals with NCDs. Most of the studies were conducted on patients who had stroke (27.3%), followed by mild cognitive impairment (22.7%) and Alzheimer's disease (13.6%). VR interventions used for cognitive rehabilitation suggested to improve cognition (e.g. memory, dual tasking, and visual attention), and secondarily to psychological functioning (e.g. reduction of anxiety, higher levels of well‐being, and increased use of coping strategies). Conclusion: VR interventions are useful to improve cognition and psychological symptoms in NCDs.